2014
DOI: 10.3109/00016489.2014.927588
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of common deafness gene mutations in deaf people from unique ethnic groups in Gansu Province, China

Abstract: The pathogenic allele frequency of the three gene mutations was different. The frequency of the GJB2 gene among the Dongxiang, Yugur, Bonan, and ethnic Han groups was 9.03%, 12.5%, 5.88%, and 12.17%, respectively. No difference was found between the ethnic groups. The frequencies of the SLC26A4 genes were 3.23%, 8.33%, 0%, and 9.81%, respectively. The mutation frequency of mtDNA1555A>G was 0%, 0%, 0%, and 6.03%, respectively. No difference was found between the ethnic groups, except for the Dongxiang and ethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Approximately 50% of childhood hearing loss is estimated to be associated with genetic contributions, and the prevalence of the m.1555 A>G mutation is 1% 4 . Furthermore, the prevalence of the m.1555 A>G mutation has been reported to be 0.42-17% in individuals with hearing loss (Table 2) 6,[15][16][17][18][19][20][21][22][23][24][25][26] . The prevalence of the m.1555 A>G mutation has been reported to be 0.08-0.7% among the general population (Table 2) [27][28][29][30][31][32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of childhood hearing loss is estimated to be associated with genetic contributions, and the prevalence of the m.1555 A>G mutation is 1% 4 . Furthermore, the prevalence of the m.1555 A>G mutation has been reported to be 0.42-17% in individuals with hearing loss (Table 2) 6,[15][16][17][18][19][20][21][22][23][24][25][26] . The prevalence of the m.1555 A>G mutation has been reported to be 0.08-0.7% among the general population (Table 2) [27][28][29][30][31][32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…The unique nomadic Chinese Yugur population is of great value for genetic studies. This population has been a target in both etiological and molecular anthropological studies ( 27 , 28 ). Accordingly, in this study, we evaluated five SNPs in the APOB gene in middle-aged and elderly members of the Chinese Yugur population, and analyzed the associations of these SNPs with HL.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation was first reported as a heterozygote variant related to ARNSHL [28]. Another study found this mutation in homozygote form [29], and then reported it in Turkey [30], and Iran [12]. These findings suggested the involvement of other genetic or environmental causes playing an important role in manifesting any disorders in this population.…”
Section: Discussionmentioning
confidence: 86%